Desenvolvimento de marcadores microssatélites e variabilidade genética em populações de Vellozia gigantea (Velloziaceae), espécie endêmica dos campos rupestres da Serra do Cipó, Minas Gerais - Ana Paula Vimieiro Martins (2011)
Vellozia gigantea is a narrowly endemic species to the campos rupestres of the Espinhaço Range, southeastern Brazil. Most of the nine known populations are inserted in the National Park of Serra do Cipó or inside the Environmental Protection Area Morro da Pedreira. Just one population is situated out of the protection area. However, the species is threatened by antropic activities. Its stems include high richness and density of epiphytes including some rare and threatened orchids, but the knowledge about its biology and history are scarce. A primary library and an enriched genomic library were constructed and seven microsatellite primers set was isolated and characterized for V. gigantea. For the polymorphic loci, the allele number ranged from 9 to 13 in the primer analyses and was about two times higher with an increase of about 20 times in the sample size. Only one locus was monomorphic. Five loci were used to estimate the variability and the genetic structure in all the known populations. The species exhibited a high level of expected heterozigosity (HE = 0.836), similar to that found for ISSR. The high inbreeding coeficiency for all populations (FIS=0.255-0.592) indicates a population substructure probably as a consequence of a restricted seed dispersion. The populations presented a moderate structuring (PT = 0.10). The results of Bayesian analysis resulted showed that the Travessão Valley is a partial barrier to gene flow, important to the variability structuring, that is grouped in two distinct genetic pool. Just one population exhibited strong evidences for a recent bottleneck. The results of this study are congruent to a wide historic distribution of the species and do not reflect actual anthropogenic impacts. These impacts could take a large number of generations to be evident, especially for large populations and long lived species. They would be probably better estimated by seeds variability research using the markers characterized in this work, and other perspectives opened by this study. Protecting entirely populations with the highest number of individuals should be a priority in the in situ conservation of the species.